Felicidad y salud: Una aproximación to well-being in the Rio de la Plata - Mariana Gerstenbluth; Máximo Rossi; Patricia Triunfo (Estudios de Economía, 2008)
– We analyze data on happiness for Argentina and Uruguay. The focus is put on self-reported health status as a key aspect in increasing happiness levels. Then, the probabilty of being happy is estimated by probit models. Results show that the main relationship is between happiness and health status. Whether this is a causal effect or a correlation, is not clear. This issue is explo red using matching methods, finding that a good health status increases the probability of being happy between 31 and 46 percentage points in Uruguay, 15 and 27 in Argentina; and 17 and 27 for the region.
Keywords: D60; I31; I12; 330; happiness; health status; matching method.; Zufriedenheit; Gesundheit; Rio de la Plata